Habitat selection patterns of common cranes Grus grus wintering in holm oak Quercus ilex dehesas of central Spain: Effects of human management (Biological Conservation, 1996)
Most of the western European population of common cranes Grus grus spends the winter in Iberian wooded dehesas, a kind of wood-pasture composed of grasslands, cereal croplands and Mediterranean scrub, densely inter- spersed with holm oak trees Quercus ilex in a savanna- like landscape. Three main types of wooded dehesas can be distinguished according to management." grazed dehesas, shrubby dehesas with occasional grazing, and cultivated dehesas without livestock. Cranes depend largely on acorns during winter and mainly select dehesas cultivated with cereals where acorn abundance is not reduced by livestock. Apparent positive effects of livestock on earth- worm abundance, the main alternative food source for cranes, does not compensate for acorn depletion. Thus, any increase in livestock grazing pressure would have a strong impact on European crane populations during their wintering in Spain.